KEBIASAAN MAKAN IKAN GARING (Tor tambra) DI SUNGAI BATANG GADIS KABUPATEN MANDAILING NATAL SUMATERA UTARA Food Habits of Garing Fish (Tor tambra) In Batang Gadis River Mandailing Natal Regency, North Sumatra Province - Adzri Qory Nullah; Pindi Patana; Ani Suryanti (AQUACOASTMARINE, 2015)
Food is an important component of the water that influences growth and development of fish. This study aims to determine the food habits of Garing fish (Tor tambra), the availability of natural forage Garing fish, and the efforts of the management of Garing fish resources in Batang Gadis river. This study was conducted in July-August 2014 at Batang Gadis river, Mandailing Natal Regency, North Sumatra. Fishing gear used nets ¾ and 1 inch. Analysis of data used the index of preponderance (IP). Material food on the digestion of Garing fish consisted of 12 genus Bacillariophyceae, 10 genus Chlorophyceae, 2 genus Conjugatophyceae, 2 genus Coscinodiscophyceae, 5 genus Cyanophyceae, 1 genus Euglenophyceae, 1 genus Mesotaeniaceae, 1 genus Oligochaeta, 1 genus Plecoptera, 1 genus Rhizopoda , insects and leaf litter. Chlorophyceae was the main food, while insect was a food supplement and Bacillariophyceae, Conjugatophyceae, Coscinodiscophyceae, Cyanophyceae, Euglenophyceae, Mesotaeniaceae, Oligocaheta, Rhizopoda and leaf litter were the extra food. Garing fish it self tends to omnivores to herbivores.Keywords : River, Index of Preponderance, Cyprinidae.